Conductive nanofluid lubricating liquid as well as preparation method and application thereof

Through electrostatic dispersion processing technology, the long-term stable dispersion of conductive nanoparticles is achieved in the conductive nanofluid lubricant by using electrostatic depolymerization-gel traction, which solves the problem of easy aggregation of conductive nanomaterials in lubricating oil and improves dispersion Uniformity and stability, adapt to different lubrication situations.

CN119307310AActive Publication Date: 2025-01-14ZHEJIANG UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411458403.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-14
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

Conductive nanomaterials are prone to spontaneous aggregation in lubricating oil, resulting in nanoparticles deposition and loss of unique functions. It is difficult for existing physical and chemical dispersion methods to achieve long-term, uniform, and stable dispersion without/low agglomeration.

Method used

By adopting the electrostatic dispersion treatment method, the conductive nanomaterial, non-polar base oil, the first gel factor and the second gel factor are added to the lubricating liquid raw material mixing system, and electrostatic dispersion is carried out under specific voltage, temperature and ultrasonic conditions. The treatment is carried out to achieve uniform and stable dispersion of conductive nanoparticles by using electrolytic depolymerization-gel traction.

Benefits of technology

The long-term stable dispersion of conductive nanoparticles in the lubricating liquid is achieved, the particle size is reduced, the uniformity and stability of the dispersion are improved, and it is adapted to different lubrication situations, and has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307310A_ABST
    Figure CN119307310A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lubricating materials, and particularly relates to conductive nanofluid lubricating liquid and a preparation method and application thereof. The conductive nanometer material capable of being charged and the non-polar base oil with low conductivity are selected as raw material components of the lubricating liquid, the lubricating liquid can be matched with an electrostatic dispersion treatment process and parameters, and by means of repulsive force among the charged conductive nanometer particles, the conductive performance of the lubricating liquid is improved. And the conductive nano material dispersed in the lubricating liquid raw material mixing system is driven to be depolymerized and uniformly dispersed in the system with smaller granularity. Furthermore, by controlling the adding variety and even the adding proportion of the gelator, the gelator can be matched with other components, and a lubricating liquid raw material mixing system and the finally prepared conductive nano-fluid lubricating liquid are adjusted to be in a liquid state with certain fluidity, so that the conductive nano-fluid lubricating liquid can be matched with conductive nano-particles with specific charge capacity under electrostatic dispersion processing parameters, and the conductivity of the conductive nano-fluid lubricating liquid is improved. And moderate dispersion and movement of the conductive nanoparticles in a lubricating liquid raw material mixing system are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of lubricating materials, and specifically relates to a conductive nanofluid lubricating liquid and a preparation method and application thereof. Background Art

[0002] Conductive nanofluid lubricants have high thermal conductivity, excellent electrical conductivity, lubricity and environmental friendliness, and have potential for application in many fields. However, due to the high surface energy and inter-particle attraction of conductive nanomaterials, they tend to spontaneously aggregate and form larger agglomerates over time. This agglomeration phenomenon causes the nanoparticles to settle in the lubricant and lose the unique functions of the nanoparticles. Therefore, improving the dispersion and stability of conductive nanomaterials in lubricants is an urgent problem to be solved.

[0003] To solve this technical problem, the commonly used methods at present mainly include physical and chemical dispersion methods. The physical dispersion method is to break the agglomerates by mechanical force or ultrasound to achieve the dispersion of nanoparticles. Common physical dispersion methods include ball milling, stirring, ultrasound, etc. Ball milling is a common physical dispersion method. The agglomerates are broken by the collision and friction of the high-speed rotating ball mill and the grinding balls to achieve the dispersion of nanoparticles. Stirring dispersion is to break the agglomerates by the shear force generated by the agitator to achieve the dispersion of nanoparticles. Ultrasonic dispersion uses the cavitation effect and mechanical effect generated by ultrasound in the liquid to break the agglomerates to achieve the dispersion of nanoparticles. The physical dispersion method has the advantages of simple operation and low cost. The chemical dispersion method is to change the surface properties of nanoparticles by adding chemical substances such as surfactants or modifiers, weaken or eliminate the interaction between particles, and thus achieve the dispersion of nanoparticles. The surface modifiers used in the chemical dispersion method include surfactants, polymers, graft modifiers, etc., which reduce the interaction between nanoparticles, increase their steric hindrance, and reduce their aggregation and sedimentation tendency through surface modification of nanoparticles. The chemical dispersion method has the advantages of good dispersion effect and high dispersion stability.

[0004] The applicant found that although the physical dispersion method can temporarily break up the agglomerates, its dispersion effect is greatly affected by the operating conditions and equipment performance, and it is difficult to achieve long-term stable dispersion. Although the chemical dispersion method can reduce the interaction between nanoparticles through surface modification, even so, the modified nanoparticles still exist in the form of clusters, especially in a complex fluid environment. Therefore, although both physical and chemical methods can be used to disperse conductive nanomaterials, in practical applications, achieving long-term, uniform, non- / low-agglomeration stable dispersion is still a technical challenge facing conductive nanofluid lubricants. Summary of the invention

[0005] In order to solve the above technical problems, the present application mainly provides a method for preparing a conductive nanofluid lubricant, which is specifically achieved through the following technical solutions: A method for preparing a conductive nanofluid lubricant comprises: performing electrostatic dispersion treatment on a lubricant raw material mixed system to obtain a conductive nanofluid lubricant; the lubricant raw material comprises, by mass percentage, 0.01-0.2wt% of conductive nanomaterial, 97.50-99.93wt% of non-polar base oil, 0.01-0.75wt% of a first gel factor and 0.05-2wt% of a second gel factor; the first gel factor comprises one or more of sodium sulfate organic matter and sodium sulfonate organic matter, and the second gel factor comprises carboxylic acid organic matter; and the conditions for the electrostatic dispersion treatment are a voltage of -2--8kV and a time of 5-60min.

[0006] Preferably, the conductive nanomaterial includes one or more of carbon-based nanomaterials, metal and metal oxide nanomaterials and conductive polymers; the first gel factor includes one or more of sodium dodecyl sulfate, sodium p-toluenesulfonate and sodium dodecylbenzenesulfonate; the second gel factor includes one or more of oleic acid, linoleic acid, linolenic acid and palmitoleic acid; the non-polar base oil includes one or more of mineral oil and alkane base oil.

[0007] Preferably, the size of the conductive nanomaterial is between 1 and 500 nm.

[0008] Preferably, the conductive nanomaterial further comprises a modifier modified on the conductive nanomaterial, and the modifier is a saturated or monounsaturated alkyl long chain.

[0009] Preferably, the main carbon chain length of the modifier differs from the single main carbon chain length of the gel factor by less than 6 carbon atoms.

[0010] Preferably, the electrostatic dispersion treatment parameters also include: temperature 20-80°C, ultrasound 200-2000W.

[0011] A conductive nanofluid lubricant is prepared by any of the above-mentioned preparation methods.

[0012] Preferably, the particle size D50 of the conductive nanomaterial in the conductive nanofluid lubricant is 50-5000 nm.

[0013] Preferably, the charge-to-mass ratio of the conductive nanofluid lubricant is 10 -3 ~10 -2 C / kg.

[0014] The conductive nanofluid lubricant prepared by any of the preparation methods described above or the use of the conductive nanofluid lubricant described in any of the above in the lubrication of mechanical equipment.

[0015] Compared with the prior art, this application has the following beneficial effects: The present application selects electrically conductive nanomaterials that can be charged and non-polar base oils with relatively low electrical conductivity as raw material components of the lubricating fluid, and can be coordinated with electrostatic dispersion treatment processes and parameters to utilize the repulsive force between charged conductive nanoparticles to drive the conductive nanomaterials dispersed in the lubricating fluid raw material mixed system to depolymerize and be evenly dispersed in the system with smaller particle sizes.

[0016] The present application controls the type and even the addition ratio of the gel factor to be added, and can cooperate with other components to adjust the lubricant raw material mixing system and the finally prepared conductive nanofluid lubricant to be a liquid with a certain fluidity. Therefore, it can be coordinated with conductive nanoparticles with a specific charge under electrostatic dispersion treatment parameters to achieve moderate dispersion and movement of conductive nanoparticles in the lubricant raw material mixing system.

[0017] The present application selects a first gel factor and a second gel factor, and sets a modifier on the conductive nanomaterial. The modifier can cooperate with the gel factor. After the static electricity of the conductive nanoparticles is dissipated, the conductive nanoparticles can be pulled, thereby ensuring the long-term dispersion stability of low-particle-size conductive nanoparticles in the conductive nanofluid lubricant, and solving the technical problem that the conductive nanoparticles have high surface energy and are easy to agglomerate and settle during long-term storage.

[0018] The present application further realizes the uniform and stable dispersion of small-sized conductive nanoparticles in a conductive nanofluid lubricant through the synergistic dispersion method of electrolytic depolymerization-gel traction. The electrostatic dispersion treatment process is simple and easy to implement. By adjusting the parameters of the electrostatic dispersion treatment within the process parameter conditions of the present application, the particle size of the carbon nanoparticles can be adjusted to adapt to different lubrication situations, and has excellent application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to clearly illustrate the embodiments, the drawings of the accompanying drawings are briefly introduced below: Figure 1 This is a schematic diagram of the deagglomeration of electrostatic dispersion in this application; Figure 2 This is a diagram showing the particle size distribution of the conductive nanoclusters in the nanofluid lubricant before and after electro-depolymerization in performance test 1; Figure 3 This is a diagram of the distribution of conductive nanoclusters in the conductive nanofluid lubricant after centrifugation in performance test 2, from left to right (a) uncharged graphene, (b) charged graphene, (c) uncharged carbon nanotubes, and (d) charged carbon nanotubes.

[0020] Figure 4 Graph showing the distribution of conductive nanoclusters in the conductive nanofluid lubricant without modifications after centrifugation in performance test 3, from left to right (a) uncharged graphene, (b) charged graphene.

[0021] Figure 5 Particle size distribution of nanoclusters in graphene oxide nanofluid lubricant at different voltages in performance test 4. DETAILED DESCRIPTION

[0022] The present application will be further described below in the form of specific embodiments. Those of ordinary skill in the art will be able to implement the present application based on these descriptions. In addition, the embodiments of the present application involved in the following description are generally only embodiments of a part of the present application, rather than all embodiments. Therefore, based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present application.

[0023] Example 1 This embodiment discloses a conductive nanofluid lubricant. The preparation method of the conductive nanofluid lubricant is as follows: (S.1) adding 0.05 g of oleic acid-modified graphene oxide (GO / OA), 0.05 g of sodium dodecyl sulfate and 0.25 g of oleic acid to 99.65 g of white oil, respectively, and stirring evenly to obtain a lubricating liquid raw material mixed system; wherein the size of the graphene oxide in the nano dimension is between 1 and 50 nm; (S.2) The obtained lubricating liquid raw material mixed system is placed in an electrolytic cell for electrostatic dispersion treatment. The electrostatic dispersion treatment parameters are DC voltage of -6kv, temperature of 60°C, ultrasound of 1000W and time of 10min. After standing at room temperature, a well-dispersed conductive nanofluid lubricating liquid is obtained.

[0024] Example 2 This embodiment discloses a conductive nanofluid lubricant. The preparation method of the conductive nanofluid lubricant is as follows: (S.1) adding 0.05 g of dodecanethiol-modified hydroxy carbon nanotubes, 0.1 g of oleic acid and 0.5 g of sodium dodecyl sulfate to 99.35 g of PEG400, respectively, and stirring evenly to obtain a lubricating liquid raw material mixed system; wherein the size of the carbon nanotubes in the nano dimension is between 1 and 50 nm; (S.2) The obtained lubricating liquid raw material mixed system is placed in an electrolytic cell for electrostatic dispersion treatment. The electrostatic dispersion treatment parameters are DC voltage -4kv, temperature 40°C, ultrasound 2000W and time 15min. After standing at room temperature, a well-dispersed conductive nanofluid lubricating liquid is obtained.

[0025] Example 3 This embodiment discloses a conductive nanofluid lubricant. The preparation method of the conductive nanofluid lubricant is as follows: (S.1) 0.05 g of graphene oxide, 1.5 g of organic amine and 0.5 g of toluene diisocyanate are added to 97.95 g of white oil respectively, and the mixture is stirred evenly to obtain a lubricating liquid raw material mixed system; the size of the graphene oxide in the nanometer dimension is between 1 and 50 nm; (S.2) The obtained lubricating liquid raw material mixed system is placed in an electrolytic cell for electrostatic dispersion treatment. The electrostatic dispersion treatment parameters are DC voltage -6kv, temperature 40°C, ultrasound 2000W and time 15min. After standing at room temperature, a well-dispersed conductive nanofluid lubricating liquid is obtained.

[0026] Example 4 This embodiment discloses a conductive nanofluid lubricant. The preparation method of the conductive nanofluid lubricant is as follows: (S.1) adding 0.01 g of dodecanethiol-modified hydroxy carbon nanotubes, 0.05 g of oleic acid and 0.01 g of sodium dodecyl sulfate to 99.93 g of PEG400, respectively, and stirring evenly to obtain a lubricating liquid raw material mixed system; wherein the size of the carbon nanotubes in the nano dimension is between 1 and 50 nm; (S.2) The obtained lubricating liquid raw material mixed system is placed in an electrolytic cell for electrostatic dispersion treatment. The electrostatic dispersion treatment parameters are DC voltage -4kv, temperature 40°C, ultrasound 2000W and time 15min. After standing at room temperature, a well-dispersed conductive nanofluid lubricating liquid is obtained.

[0027] Example 5 This embodiment discloses a conductive nanofluid lubricant. The preparation method of the conductive nanofluid lubricant is as follows: (S.1) 0.2 g of dodecanethiol-modified hydroxy carbon nanotubes, 1.55 g of oleic acid and 0.75 g of sodium dodecyl sulfate are added to 97.5 g of PEG400, and the mixture is stirred evenly to obtain a lubricating liquid raw material mixed system; wherein the size of the carbon nanotubes in the nanometer dimension is between 1 and 50 nm; (S.2) The obtained lubricating liquid raw material mixed system is placed in an electrolytic cell for electrostatic dispersion treatment. The electrostatic dispersion treatment parameters are DC voltage -8kv, temperature 20°C, ultrasound 2000W and time 5min. After standing at room temperature, a well-dispersed conductive nanofluid lubricating liquid is obtained.

[0028] Example 6 This embodiment discloses a conductive nanofluid lubricant. The preparation method of the conductive nanofluid lubricant is as follows: (S.1) adding 0.01 g of dodecanethiol-modified hydroxy carbon nanotubes, 2 g of oleic acid and 0.01 g of sodium dodecyl sulfate to 97.98 g of PEG400, respectively, and stirring evenly to obtain a lubricating liquid raw material mixed system; wherein the size of the carbon nanotubes in the nano dimension is between 1 and 50 nm; (S.2) The obtained lubricating liquid raw material mixed system is placed in an electrolytic cell for electrostatic dispersion treatment. The electrostatic dispersion treatment parameters are DC voltage -2kv, temperature 80℃, ultrasound 200W and time 60min. After standing at room temperature, a well-dispersed conductive nanofluid lubricating liquid is obtained.

[0029] Comparative Example 1 The difference between this comparative example and Example 1 is that the preparation steps of the conductive nanofluid lubricating liquid do not include step (S.2).

[0030] Comparative Example 2 The difference between this comparative example and Example 2 is that the preparation steps of the conductive nanofluid lubricating liquid do not include step (S.2).

[0031] Comparative Example 3 The difference between this comparative example and Example 3 is that the preparation steps of the conductive nanofluid lubricating liquid do not include step (S.2).

[0032] Performance Test 1 This performance test measures the particle size distribution of nanoclusters in the conductive nanofluid lubricating fluid obtained in Examples 1 and 2 and Comparative Examples 1 and 2, and the measurement method is: Zeta potential and particle size analysis. The measurement results are detailed in Figure 2 , by observing Figure 2 It can be found that in Examples 1 and 2, the particle size of the conductive nanoclusters can be greatly reduced by electrostatically dispersing the lubricating liquid raw material mixed system. This means that the present application can cooperate with the electrostatic dispersion treatment process and parameters through the selection and ratio design of the lubricating liquid raw material. The charged conductive nanomaterial can be depolymerized and dispersed in the lubricating liquid raw material mixed system with certain flow properties under the action of the electric field force and the coulomb within the agglomeration. Therefore, the conductive nanoparticles in the lubricating liquid raw material mixed system are smaller.

[0033] Performance Test 2 In this performance test, the conductive nanofluid lubricating liquid obtained in Examples 1 and 2 and Comparative Examples 1 and 2 was centrifuged at 2000 r / min for 5 min, and then the dispersion of the conductive nanofluid lubricating liquid was checked to obtain Figure 3 By observing Figure 3It can be found that after high-speed centrifugation, the conductive nanomaterials in Comparative Examples 1 and 2 have been aggregated in large quantities and formed a sediment at the lower end of the test tube, while there are only a few aggregates in the conductive nanofluid lubricating liquid obtained in Examples 1 and 2. It can be seen that the present application selects the first gel factor and the second gel factor, and sets a modifier on the conductive nanomaterial. The modifier can cooperate with the first gel factor. After the static electricity of the conductive nanoparticles dissipates, the low-particle-size conductive nanoparticles can be strongly pulled, thereby ensuring the long-term dispersion stability of the low-particle-size conductive nanoparticles in the conductive nanofluid lubricating liquid, effectively overcoming the problem of easy aggregation and precipitation due to the high surface energy of the conductive nanoparticles, and improving the stability of the nanomaterial under long-term storage conditions.

[0034] Performance Test 3 In this performance test, the conductive nanofluid lubricant obtained in Example 3 and Comparative Example 3 was centrifuged at 2000 r / min for 5 minutes, and then the dispersion of the conductive nanofluid lubricant was checked to obtain the dispersion. Figure 4 By observing Figure 4 It can be found that when no modifier is provided on the conductive nanomaterial, the conductive nanofluid lubricant prepared by electrostatic dispersion treatment can achieve relatively stable dispersion.

[0035] Performance Test 4 This performance test is based on Example 1, and the DC voltage is adjusted to 0, -1kv, -2kv, -4kv, -6kv, -8kv and -10kv respectively, and the particle size of the nanoclusters in the conductive nanofluid lubricant is tested. Figure 5 .observe Figure 5 It can be found that after applying electrostatic dispersion treatment to the specific gel system in Example 1, the particle size is greatly reduced. When the voltage is set to -6kv, the particle size reaches the minimum; further, when the voltage is set to -10kv, the particle size increases instead. After analysis, the applicant believes that excessively high charge density may increase the Brownian motion of the particles, promote particle collisions to form larger agglomerates, and ultimately lead to an increase in the average particle size.

Claims

1. A method for preparing a conductive nanofluid lubricant, characterized in that: include: Performing electrostatic dispersion treatment on the lubricating liquid raw material mixed system to obtain a conductive nanofluid lubricating liquid; Calculated in terms of mass percentage, the lubricating fluid raw material includes 0.01-0.2wt% of conductive nanomaterial, 97.50-99.93wt% of non-polar base oil, 0.01-0.75wt% of a first gel factor and 0.05-2wt% of a second gel factor; the first gel factor includes one or more of sodium sulfate organic matter and sodium sulfonate organic matter, and the second gel factor includes carboxylic acid organic matter; the conditions for the electrostatic dispersion treatment are a voltage of -2-8kV and a time of 5-60min.

2. The method for preparing a conductive nanofluid lubricant according to claim 1, characterized in that: The conductive nanomaterial includes one or more of carbon-based nanomaterials, metal and metal oxide nanomaterials and conductive polymers; the first gel factor includes one or more of sodium dodecyl sulfate, sodium p-toluenesulfonate, and sodium dodecylbenzenesulfonate; the second gel factor includes one or more of oleic acid, linoleic acid, linolenic acid, and palmitoleic acid; the non-polar base oil includes one or more of mineral oil and alkane base oil.

3. The method for preparing a conductive nanofluid lubricant according to claim 2, characterized in that: The size of the conductive nanomaterial is between 1 and 500 nm.

4. The method for preparing a conductive nanofluid lubricant according to claim 1, characterized in that: The conductive nanomaterial further comprises a modifier modified on the conductive nanomaterial, and the modifier is a saturated or monounsaturated alkyl long chain.

5. The method for preparing a conductive nanofluid lubricant according to claim 4, characterized in that: The main carbon chain length of the modifier differs from the single main carbon chain length of the first gel factor by less than 6 carbon atoms.

6. The method for preparing a conductive nanofluid lubricant according to claim 1, characterized in that: The electrostatic dispersion treatment parameters also include: temperature 20-80°C, ultrasound 200-2000W.

7. A conductive nanofluid lubricant, characterized in that: The preparation method is described in any one of claims 1 to 6.

8. Use of the conductive nanofluid lubricant according to claim 7 in lubrication of mechanical equipment.

Citation Information

Patent Citations

  • Nanofluid lubricating liquid and preparation method thereof

    CN115637188A

  • Surface-treated metal sheet which excels in workabilit, electrical conductivity and corrosion resistance, and method of producing the same.

    KR1019940011661A

  • Colloid, method of obtaining colloid or its derivatives and applications thereof

    WO2005080030A2

  • Aqueous graphite lubricant compositions

    WO2023107321A1